Prevalence and determinants of atypical presentation of acute coronary syndrome. - Pinto, David (2011)
Knowledge of the characteristics of patients with atypical presentation of acute coronary syndromes may contribute to increased sensitivity in diagnosis in a given population. The purpose of this study is to quantify the prevalence of atypical presentation, to identify its determinants, and to describe the presenting symptoms in cases of acute coronary syndrome at the emergency department of Hospital São João, Porto.Systematic sample of 288 emergency admissions with a confirmed diagnosis of acute coronary syndrome in 2007. Atypical presentation was defined as absence of chest pain and/or syncope.The prevalence of atypical presentation was 20.5% [95% confidence interval (CI): 16.0 to 25.5], with no important variation by gender. It increased with age and was more frequent in cases of ST-segment elevation myocardial infarction. In multivariate analysis, atypical presentation was associated with age [>70 versus ≤ 50 years, odds ratio (OR)=3.45; 95%CI: 1.03-11.61] and it was about four times less likely in the presence of history of ischemic heart disease, hypertension, dyslipidemia and smoking. A history of heart failure was independently associated with a higher likelihood of acute coronary syndrome with atypical presentation (OR = 4.15, 95%CI 1.50-11.46). Among the 223 cases who had chest pain or discomfort, a growing, oppressive, prolonged (longer than 30 minutes), recurrent and episodic pain prevailed. Among other symptoms, dyspnea was the most frequently reported, either as the main symptom in cases of atypical presentation or concurrently with typical symptoms.Factors associated with atypical presentation are consistent with those described in other populations. Using routine clinical data allowed access to a large data base on a representative sample of patients admitted to the emergency department of a third-level hospital that serves a large part of the local urban population. In medical records, data are unstandardized and heterogeneous in validity and detail.One fifth of the episodes of acute coronary syndrome have atypical presentation, and this proportion is higher in older ages. Previous history of ischemic heart disease or its classical risk factors are associated with typical symptoms, while heart failure is associated with atypical presentation. Presentation in atypical cases is highly variable and does not allow the identification of a pattern that would justify lowering the threshold for suspicion of acute coronary syndrome.